Case report: Continuous infusions of ceftazidime-avibactam and aztreonam in combination through elastomeric infusors for 12 weeks for the treatment of bone and joint infections due to metallo-β-lactamase producing Enterobacterales - Merad, Yanis; Conrad, Anne; Brosset, Sophie; Schmidt, Axel; Hanriat, Camille; Lustig, Sebastien; Laurent, Frederic; Kolenda, Camille; Roussel-Gaillard, Tiphaine; Batailler, Cecile; Ferry, Tristan; , Lyon BJI Study group (Frontiers in Medicine, 2023)
Among carbapenem-resistant Enterobacterales, metallo-beta-lactamase-producing strains represent a growing therapeutic challenge. While the association of aztreonam and ceftazidime-avibactam has been investigated in recent years for treatment of infections involving these strains, little to no clinical data supports the use of this association for treatment of bone and joint infections. We report two cases of complex bone and joint infections involving metallo-beta-lactamase-producing Enterobacterales, successfully treated at our referral center with aztreonam and ceftazidime-avibactam for 12 weeks in continuous infusions through elastometric infusors.